KINERJA ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH Studi Tentang Kinerja Anggota Dewan Perwakilan Rakyat Daerah Prespektif Opini Publik di Kota Tasikmalaya - Taufik Nurohman; Wiwi Widiastuti (Jurnal Ilmu Politik dan Pemerintahan, 2011)
This study entitled "PERFORMANCE OF MEMBERS OF THE HOUSE OF REPRESENTATIVES (Performance Studies Member of Legislative Assembly Perspective Public Opinion in the City Tasikmalaya)". The purpose of this study is to investigate in depth and obtain a descriptive about to find out public opinion on Parliament's performance in terms of the City Tasikmalaya resposivitas, reliability and accountability. The research method used was qualitative-descriptive, with the informant selection techniques using purposive sampling. Collecting data through in-depth interviews, observation, and documentary studies. The method of analysis used is Interactive Analysis Model to the validity of data was tested using Trianggulasi Sources. The results showed that by looking at indicators of responsiveness, reliability, accountability and implementation of the functions of Parliament is seen that legislators Tasikmalaya City has not shown a good performance. When the members of the City Legislature Tasikmalaya showed good performance and the public quite satisfied with its performance then it did not rule on the coming election period they will be re-elected, but if this is the opposite then it is possible to describe the members of this council will be left and will not be selected again by the voters in the upcoming election period.